E-sports: efeitos de auto fala no incremento de habilidades no jogo League of Legends - Santos, Alberto da Silva (2018)
The objective of this study was to extend and apply classic procedures of Behavioral Sport Psychology to new sports contexts, the electronic sports. The so-called e-sports are sporting modalities that have had their growth propitiated by the technological development of computers and internet networks. Among these new electronic modalities are the League of Legends, a game of the MOBA category whose championships have been frequently cited in media and sports channels, which used to be devoted only to the broadcasting of news about traditional sports. Teams that compete at national and international level rely on technical support professionals specialized in sports performance; among these professionals there is also the Sport Psychologist. In an expanding field the variables previously present in the traditional sports environment are also found in the competitive electronic sports environment. Topics such as anxiety, concentration and other psychological aspects are seen as relevant to the good performance of cyber athletes. From the classic behavioral psychology procedures of the sport the self talk was the independent variable used in the procedure of this study. The research problem was to identify the effects of the isolated, self-chosen, selfchosen, participant-chosen use of the last hit of an electronic and complex MOBA game, represented by the League of Legends, by participants with beginner level of experience. Four amateur practitioners participated in the study, two submitted to the experimental variable (self talk) and two as control. In a variable interval reinforcement (VI) + Limited Hold scheme, the establishment of self-talk as a discriminative stimulus for the click-on-target response at the correct time produced some changes in the response of the participants who underwent the experimental condition, which merited an analysis more detailed. The results obtained contribute to the literature of an expanding area and can serve as a starting point for the development of interventions in the applied field; still allow to identify adjustments so that the use of self talk may be pertinent to the target behavior chosen. Verification of the correlation between verbal response and non-verbal response has shown that in complex situations with a given class of responses required at a very high frequency per minute, the use of continuous self-talk may not be helpful. However, its use in a more comprehensive and timely way can contribute to the planning of actions and the chaining of complex responses